Formirovanie optimal'noj boevoj gotovnosti boksëra na predsorevnovatel'nom etape sportivnoj podgotovki - Sinitsyn, D. K.; Zimin, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Currently, the training of the boxer requires the inclusion of the relevant techniques and developments. Not only to improve the athlete`s skill, but also to improve his psychological preparation. This can be achieved with the help of competent planning of the training process of the boxer, which will also be aimed at studying his nervous system.